The Kingdom of God Is at Hand : The Christian Commonwealth in Georgia, 1896-1901 - Kallman, Theodore (Book collections on Project MUSE., 2021)
"In Kingdom of God Theodore Kallman illuminates the brief life of a Christian socialist community founded by four men--a minister, an editor, a professor, and an engineer--on a worn-out cotton plantation just outside of Columbus, Georgia in 1896. While Christian Commonwealth only lasted until 1900, its combination of religious communitarianism and socialist ideology proved attractive to many. It was a place where women enjoyed a sort of political equality and where its school--open to all white students of Muscogee County--emphasized a critique of private property. Kallman explains how a particular brand of Tolstoyan anarchism inspired by the Russian novelist's philosophical treatise The Kingdom of God is Within You (1894) and Christ's Sermon on the Mount took root in west-central Georgia and attracted attention from famous onlookers--Leo Tolstoy and Jane Addams included. In Kallman's capable hands, what appears to be merely a blip barely worth mentioning for historians of Georgia and the larger United States, instead emerges as a story that has much to teach us about Gilded Age America and provides necessary context for the surging interest in America's socialist past"--